Risk of Immunomediated Adverse Events and Loss of Response to Infliximab in Elderly Patients with Inflammatory Bowel Disease: A Cohort Study of the ENEIDA Registry. (3rd December 2021) - Calafat, Margalida; Mañosa, Míriam; Ricart, Elena; Nos, Pilar; Iglesias-Flores, Eva; Vera, Isabel; López-Sanromán, Antonio; Guardiola, Jordi; Taxonera, Carlos; Mínguez, Miguel; Martín-Arranz, M Dolores; de Castro, Luisa; et al.
Abstract: Background and Aims: Immunomediated adverse events [IAEs] are the most frequently reported infliximab [IFX]-related adverse events. Combination therapy may reduce their incidence, although this strategy is not recommended in elderly patients. We aimed to compare the rates of IFX-related IAEs and loss of response [LOR] in elderly and younger patients. Methods: Adult patients in the ENEIDA registry who had received a first course of IFX therapy were identified and grouped into two cohorts regarding age at the beginning of treatment [over 60 years and between 18 and 50 years]. The rates of IAEs and LOR were compared. Results: In total, 939 patients [12%] who started IFX over 60 years of age and 6844 [88%] below 50 years of age were included. Elderly patients presented a higher proportion of AEs related to IFX [23.2% vs 19%; p = 0.002], infections [7.1% vs 4.3%; p < 0.001] and neoplasms [2.2% vs 0.5%; p < 0.001]. In contrast, the rates of IAEs [14.8% vs 14.8%; p = 0.999], infusion reactions [8.1% vs 8.1%; p = 0.989], late hypersensitivity [1.3% vs 1.2%; p = 0.895], paradoxical psoriasis [1% vs 1.5%; p = 0.187] and drug-induced lupus erythematosus [0.6% vs 0.7%; p = 0.947] were similar in elderly and younger patients. LOR rates were also similar between the two groups [20.5% vs 19.3%; p = 0.438]. In the logistic regression analysis, IFX monotherapy, extraintestinal manifestations and female gender were the only risk factors for IAEs, whereas IFX monotherapy, extraintestinal manifestations and Crohn's disease were risk factors for LOR. Conclusions: Elderly patients with inflammatory bowel disease have a similar risk of developing IFX-related IAEs and LOR to that of younger patients.